2011
DOI: 10.1016/j.peva.2011.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the file hosting ecosystem: A view from the edge

Abstract: We present a comprehensive, longitudinal characterization study of the file hosting ecosystem using HTTP traces collected from a large campus network over a one-year period. We performed detailed multi-level analysis of the usage behaviour, infrastructure properties, content characteristics, and user-perceived performance of the top five services in terms of traffic volume, namely RapidShare, Megaupload, zSHARE, MediaFire, and Hotfile. We carefully devised methods to identify user clickstreams in the HTTP trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 29 publications
1
25
0
4
Order By: Relevance
“…In both cases a ground truth sample is needed, which is a topic addressed by [22]. In [7] and [12] the authors use DPI to obtain information from the HTTP headers. Our approach is orthogonal to these works, since we are interested in extending IP flow records with HTTP data.…”
Section: Related Workmentioning
confidence: 99%
“…In both cases a ground truth sample is needed, which is a topic addressed by [22]. In [7] and [12] the authors use DPI to obtain information from the HTTP headers. Our approach is orthogonal to these works, since we are interested in extending IP flow records with HTTP data.…”
Section: Related Workmentioning
confidence: 99%
“…They are typically implemented in a centralised fashion with thousands of servers located in computing centres [2,16,20]. According to previous studies, there are more than 300 OCHs [12].…”
Section: Background: the Och Ecosystemmentioning
confidence: 99%
“…A file can be downloaded only when the corresponding download link is known. Therefore, uploaders who wish to disseminate their files post the download links on blogs, social networking sites, discussion boards, or they even submit their links to specialised search engines such as Filestube [2,12,15,16]. Mahanti et al [15] observed OCHs were receiving incoming traffic from up to 8,000 indexing sites.…”
Section: Background: the Och Ecosystemmentioning
confidence: 99%
See 2 more Smart Citations